Sickness Profile of the Children Attending Paediatric Out Patient Department at Combined Military Hospital, Dhaka (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Children are the major victims of mortality and morbidity in our society. Though Bangladesh has achieved significant success in reducing mortality of children over the past few decades, but still it is alarming.Objective: To determine the sickness profile of the children under 12 years attending paediatric outpatient department at combined Military Hospital (CMH), Dhaka.Methods: This descriptive cross-sectional study was conducted from July to December 2012 to determine the sickness profile of the children under 12 years attending paediatric outpatient department at CMH, Dhaka. A total of 143 children were selected for this study and data were collected with a semistructured questionnaire and check list by face-to-face interview of the parents and reviewing medical records of the children.Results: Among the subjects, 60.1% were male and 39.9% were female with mean age 4.8(±3.6) years. Regarding mother’s education, 62.2% were SSC or equivalent qualified, 23.1% HSC, 0.7% Diploma and 4.9% were Graduated or above. Average family size of the children was 4 (±0.7). Most of the mothers (97.2%) were housewives. The diseases suffered by children included respiratory diseases (43.4%), gastro intestinal diseases (17.5%), pyrexia (16.8%), neurological diseases (14.0%) and non-communicable diseases (8.4%). Respiratory diseases (43.4%) were more common in children of housewives’ mother (43.9%) while neurological diseases (14.0%) were prevalent in children of serving mother and these differences were statistically significant (P=0.027). Regarding age and diseases, respiratory diseases were more in